UMPSA@Bumi Kenyalang ‘Kembara Prihatin’ Programme for school students around Belaga - Nor Salwana, Mohammad Idris (UMPSA, 2024)
BELAGA, SARAWAK, 16 August 2024 – The UMPSA@Bumi Kenyalang 2.0 Kembara Prihatin Programme inspires school students to aim higher and pursue their dreams through various fun activities, organized in collaboration with Yayasan Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) volunteers and strategic partners, including the MARA Skills Institute (IKM), Bintulu, recently in Belaga.